To the problem of multiplicativity of canonical diagonal forms of matrices over the domain of principal ideals - Prokip, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We study the structure of nonsingular matrices over the domain of principal ideals that possess the property of multiplicativity of canonical diagonal forms. In particular, we establish necessary and sufficient conditions of multiplicativity of canonical diagonal forms of nonsingular matrices over this domain.